On convergence of a sequence of mappings with inverse modulus inequality to a discrete mapping - Sevost’yanov, E.; Targonskii, V. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We consider mappings satisfying the Poletsky-type inverse inequality in a domain of the Euclidean space. It is shown that the uniform limit of the family of these mappings is a discrete mapping. We separately consider domains that are locally connected on their boundaries and regular domains in the quasiconformal sense.